2003
DOI: 10.1007/s00429-002-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression during rat fetal development of GLUT12 – a member of the class III hexose transporter family

Abstract: Glucose is an essential molecule for most mammalian cells, and is particularly important during fetal development, when cells are rapidly dividing and differentiating. In rats, GLUT1 is present at high levels in most fetal tissues, with levels decreasing after birth. We used immunohistochemistry to localise GLUT12 protein, a recently identified member of the sugar transporter family, and GLUT1 during rat fetal development. GLUT12 staining was observed in heart muscle from gestational days 15 to 21. GLUT12 stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Immunohistochemical staining of the rat fetus from gestational day 13 to 21 shows weak GLUT12 expression in the epithelial cell membrane of bronchioles at gestational day 19, which increases in intensity by day 21. Consistent with mRNA expression studies, GLUT1 protein was also observed in the airways at gestational day 19, decreasing in intensity at day 21 [57]. GLUT1 protein has also been detected in the alveolar epithelium of the fetal rat, although to date, GLUT1 protein has not been identified in either the airways or distal lung of the adult rat [59].…”
Section: Developmental Differences In Lung Glucose Transportsupporting
confidence: 63%
“…Immunohistochemical staining of the rat fetus from gestational day 13 to 21 shows weak GLUT12 expression in the epithelial cell membrane of bronchioles at gestational day 19, which increases in intensity by day 21. Consistent with mRNA expression studies, GLUT1 protein was also observed in the airways at gestational day 19, decreasing in intensity at day 21 [57]. GLUT1 protein has also been detected in the alveolar epithelium of the fetal rat, although to date, GLUT1 protein has not been identified in either the airways or distal lung of the adult rat [59].…”
Section: Developmental Differences In Lung Glucose Transportsupporting
confidence: 63%
“…Of the 14 SLC2 gene family members, expression of Glut1, Glut2, Glut3, Glut8 and Glut12 (also known as Slc2a1, Slc2a2, Slc2a3, Slc2a8 and Slc2a12) is detected in preimplantation mouse embryos [13][14][15][16][17][18]. GLUT12 protein is not detected in early postimplantation embryos, but it is detected later, during fetal development [17,19]. Only expression of Glut1, Glut2 and Glut3 has been detected during the stage of postimplantation development that is susceptible to diabetic embryopathy (day 7.5) [12,13,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…GLUT12 cDNA has also been cloned from mouse and cow, presenting respectively 83 and 87 % homology with the human isoform [24,49], and expression of GLUT12 has been reported in rat [18], horse [38] and dog [41].…”
Section: Structure and Tissue Distributionmentioning
confidence: 99%
“…Its mRNA is abundant in skeletal muscle, heart and prostate, and it is present at low levels in brain and kidney [30]. In rat, expression of GLUT12 protein has been described during foetal development in skeletal muscle, brown adipose tissue, heart, foetal chondrocytes, lung, kidney [18], mammary gland during pregnancy [19] and kidney distal tubes and collecting ducts [15]. In cow, its mRNA expression is abundant in spleen and skeletal muscle, less expressed in kidney, testis and mammary gland, and even lower expressed in liver, lung and intestine [24].…”
Section: Structure and Tissue Distributionmentioning
confidence: 99%
See 1 more Smart Citation